Mould design and characterization of Kenaf fiber honeycomb core- reinforced epoxy composites for aerospace applications - Manan, Nor Hafizah (2017)
Sandwich structures with honeycomb core are known to significantly improve stiffness at lower weight and possess high flexural rigidity. These structures are found wide applications in aerospace as part of the primary structures as well as the interior paneling and flooring. High performance aluminum and aramid are typical material used for the purpose of honeycomb core whereas in addition to other industries, other materials such as fiber glass, carbon fiber, Nomex, and also Kevlar reinforced with polymer are used. Recently, growing interest in developing composite structures with natural fiber reinforcement has also spurred research in natural fiber honeycomb material. The performances of honeycomb cores are dictated by cell size, wall thickness and core thickness. In term of research purposes, it has been reported that the honeycomb core are fabricated using single core mould however, the mould is not specifically for aerospace application. In this work, a single core mould for honeycomb core is designed and fabricated as per aerospace standard. In terms of fiber direction, the majority of the previous works have generally emphasized on the usage of random chopped fiber and few are reported on development of honeycomb structure using unidirectional fiber as the reinforcement. This is mainly due to its processing difficulties which usually involve several stages to account for the arrangement of fibers and curing. In this work, honeycomb cores of neat epoxy, random chopped strand kenaf/epoxy and unidirectional kenaf/epoxy are introduced and their mechanical properties are compared in term of tensile test, edgewise compression test, flatwise compression test, and flexural test. In order to compare the performances of honeycomb in term of fiber orientations, the density and volume fraction are ensured to be the same for all samples. From the result, the coupon specimen of unidirectional kenaf/epoxy has high tensile strength which is 43.18% more than random kenaf/epoxy. In comparing between honeycomb core biocomposites, the honeycomb core of random kenaf/epoxy is superior to unidirectional kenaf/fiber in term of edgewise compressive strength, flatwise compressive strength and flexural strength which is 21%, 17.7%, and 88.67% respectively. Failure modes analysis shows that unidirectional kenaf fiber suffer fiber breakage, fiber pulled out, obvious stress lines, matrix cracking, cohesion failure and fiber buckling. However, in random kenaf fiber the fracture modes are defined only by fiber breakage, fiber splitting, obvious stress lines, fiber pulled out and compaction.